2002
DOI: 10.1007/s00134-002-1518-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the humidification device on the work of breathing during noninvasive ventilation

Abstract: In patients receiving NIV for moderate to severe acute hypercapnic respiratory failure, the use of HME lessens the efficacy of NIV in reducing effort compared to HH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 42 publications
1
78
0
5
Order By: Relevance
“…It has been shown that, in acute studies [19,20] and compared to HH, the HME may significantly increase dead space, work of breathing and carbon dioxide retention during an episode of acute respiratory failure requiring NIMV treatment, and this may also interfere with triggering functioning. Acute changes in Pa,CO 2 during NIMV may not predict a chronic effect, as demonstrated, for example, by HILL et al [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, in acute studies [19,20] and compared to HH, the HME may significantly increase dead space, work of breathing and carbon dioxide retention during an episode of acute respiratory failure requiring NIMV treatment, and this may also interfere with triggering functioning. Acute changes in Pa,CO 2 during NIMV may not predict a chronic effect, as demonstrated, for example, by HILL et al [21].…”
Section: Discussionmentioning
confidence: 99%
“…Lellouche et al 79 reported that minute ventilation was significantly higher with an HME than with heated humidifier for a similar P aCO 2 . Moreover, the HME was associated with a greater increase in work of breathing and indexes of patient effort.…”
Section: The Humidifier and Asynchronymentioning
confidence: 95%
“…In addition, bronchial mucosa may be injured by dry gas with dry secretions difficult to cough. Heated humidifiers are usually preferred to HMI that offer more inspiratory resistances and dead space in NIV (5,6).…”
Section: Equipmentmentioning
confidence: 99%